Factors of adherence to lifestyle modification in older patients with cardiovascular comorbidity. (14th October 2021) - Efremova, E; Shutov, A M; Skorodumova, E G
Abstract: : Lifestyle modification is one of the leading strategies for successful therapy. Older patients are characterized by comorbidity and gerontological syndromes that result in low adherence to lifestyle modifications. The aim of this study was to investigate the factors of adherence to lifestyle modification in older patients with cardiovascular comorbidity. Materials and methods: 344 older patients with cardiovascular disease (171 females, mean age 69, 5±7, 6 years) were examined. Arterial hypertension had 330 (95, 9%) patients, coronary heart disease - 298 (86, 6%), chronic heart failure - 240 (69, 8%), diabetes mellitus – 100 (29%). Arterial hypertension was defined according to ESC Guidelines for the diagnosis and treatment of arterial hypertension, 2018. An integral indicator of adherence to a healthy lifestyle was assessed, including smoking status, physical activity, consumption of fruits and vegetables, and salt restriction. The level of education, income, personal profile (MMPI scale), cognitive status (MMSE scale) were estimated. Results: 145 (42.2%) older patients with cardiovascular comorbidity had high and satisfactory adherence to lifestyle modification. Women more often had a high and satisfactory adherence to adherence to lifestyle modification compared to men: 85 (49.7%) and 60 (34.6%), resp., χ 2 =7.96; p=0.005. The presence of diabetes mellitus was associated with high and satisfactory adherence to lifestyle modification (OR 2.39; 95% CI 1.29–4.42; p=0.005). Older patients with high adherence to lifestyle recommendations had a higher MMSE score (26.9±2.7 and 24.7±3.7 scores, resp., p=0.01) and lower personality profile indices on the depression scale (MMPI) (52.2±9.8 and 60.6±11.1 T-scores, resp., p=0.01) compared to patients with low adherence. There were no differences from education, income, and marital status (p>0.05). When constructing classification trees in older patients with cardiovascular comorbidity diabetes mellitus was an independent factor for satisfactory and high adherence to lifestyle modification, in the absence - female sex (sensitivity - 84.8%; specificity - 37.5% (AUC = 0.64); p=0.001 for model; χ 2 =20.2, p=0.0002). Conclusions: More than half of older patients with cardiovascular comorbidity are characterized by low adherence to lifestyle modification. Diabetes mellitus is the most significant predictor of a high degree of adherence to lifestyle modification in older patients with cardiovascular comorbidity. Funding Acknowledgement: Type of funding sources: None.